2019
DOI: 10.1007/s10712-019-09524-0
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Spectroscopy for Soil Mapping and Monitoring

Abstract: There is a renewed awareness of the finite nature of the world's soil resources, growing concern about soil security and significant uncertainties about the carrying capacity of the planet. Regular assessments of soil conditions from local through to global scales are requested, and there is a clear demand for accurate, up-to-date and spatially referenced soil information by the modelling scientific community, farmers and land users, and policy-and decision-makers. Soil and imaging spectroscopy, based on visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 175 publications
1
65
0
1
Order By: Relevance
“…It is likely that the LUCAS samples in other European regions are not numerous enough [29] or not representative of the soil variability of the investigated area. Until now, remote sensing or airborne spectroscopy was used for small areas that are mostly rather homogeneous in parent material and soil forming factors [30]. Castaldi et al [9] demonstrated that sampling strategies based on the feature space, where the spectral bands were used as ancillary data, were most efficient when the Demmin area was stratified, according to 'soil scapes,' i.e., distinguishing sandy and clay topsoil (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the LUCAS samples in other European regions are not numerous enough [29] or not representative of the soil variability of the investigated area. Until now, remote sensing or airborne spectroscopy was used for small areas that are mostly rather homogeneous in parent material and soil forming factors [30]. Castaldi et al [9] demonstrated that sampling strategies based on the feature space, where the spectral bands were used as ancillary data, were most efficient when the Demmin area was stratified, according to 'soil scapes,' i.e., distinguishing sandy and clay topsoil (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Castaldi et al [9] demonstrated that sampling strategies based on the feature space, where the spectral bands were used as ancillary data, were most efficient when the Demmin area was stratified, according to 'soil scapes,' i.e., distinguishing sandy and clay topsoil (Figure 1). Other factors that are likely to improve the SOC prediction models are the absence of a soil crust (since it does not represent the spectral signal of the topsoil [30] and the large variability in SOC content). Gomez et al [31] reported that, in contrast to clay and calcium carbonate content, SOC could not be predicted in Mediterranean environments due to the very low and rather constant SOC content.…”
Section: Discussionmentioning
confidence: 99%
“…The explicit representation of water reservoirs -and other infrastructure -is indeed likely to result in more realistic soil parameters, a hypothesis whose verification depends on the availability of observations about soil physical properties for large spatial domains. In turn, this highlights the importance of studies aimed to infer such properties from remotely sensed images (Chang and Islam, 2000;Chabrillat et al, 2019). A related topic that may also deserve future research is the robustness of these models with respect to changes in the operations or physical characteristics of dams.…”
Section: Scenariomentioning
confidence: 96%
“…Firstly, optical RS captures only the properties of the uppermost centimeters of the top-soil and cannot provide information about the entire soil body. Secondly, atmospheric effects and sensor constraints [119], soil moisture contents [120], soil roughness, or soil surface coverage by vegetation or plant residues [117] can interfere with the spectral signal [121].…”
Section: Pedologymentioning
confidence: 99%
“…See Chabrillat et al [121] for a recent review of the potential of upcoming spaceborne hyperspectral imagery for global soil mapping and monitoring. Table 2 provides an overview of the recent and future spaceborne hyperspectral missions with their sensor characteristics deriving soil characteristics and traits.…”
Section: Pedologymentioning
confidence: 99%